Activated Ni–O–Ir Enhanced Electron Transfer for Boosting Oxygen Evolution Reaction Activity of LaNi1‐xIrxO3. Issue 50 (31st October 2022) - Li, Jianyi; Zheng, Lirong; Huang, Bolong; Hu, Yang; An, Li; Yao, Yaxiong; Lu, Min; Jin, Jing; Zhang, Nan; Xi, Pinxian; Yan, Chun‐Hua
Abstract: Tuning the structure of the active center of catalysts to atomic level provides the most efficient utilization of the active component, which plays an especially important role for precious metals. In this study, the liquid phase ion exchange method is used to introduce atomic Ir into LaNiO3 perovskite oxide, which shows excellent catalytic performance in the oxygen evolution reaction (OER). The catalyst, LaNi0.96 Ir0.04 O3, with the optimal concentration of Ir, displays an overpotential of just 280 mV at 10 mA cm −2 . The introduced Ir enriches the surface electron density significantly, which not only improves site‐to‐site electron transfer between O and Ni sites but also allows stable adsorption of the intermediates. The results of cyclic voltammetry tests reveal the superior overpotential and remarkable efficiency of the OER process because of the strong interactions in Ni–O–Ir. Moreover, the Ir atom inhibits the participation of a lattice oxygen oxidation mechanism (LOM) in LaNiO3 that guarantees the stability of the catalyst in alkaline conditions. It is anticipated that this work will be instrumental for the preparation and study of a broad range of atomic metal‐doped perovskite oxides for water splitting. Abstract : In this work, atomic‐level Ir doped perovskite oxide LaNiO3 are successfully synthesized and characterized in which the LaNi0.96 Ir0.04 O3 exhibits an overpotential of 280 mV at j = 10 mA cm −2 in alkaline oxygen evolution reaction (OER) electrocatalysis, which is superior to the commercial IrO2 . This report shows the operability of adjusting atomic doping levels to prompt the exploration of more active sites for the further development of high‐efficiency perovskite catalysts and deepens insights into the understanding of the major processes of the structural transformation during the OER process.